2009
DOI: 10.1007/s11302-009-9174-y
|View full text |Cite
|
Sign up to set email alerts
|

Adenosine A2A agonist and A2B antagonist mediate an inhibition of inflammation-induced contractile disturbance of a rat gastrointestinal preparation

Abstract: Adenosine can show anti-inflammatory as well as pro-inflammatory activities. The contribution of the specific adenosine receptor subtypes in various cells, tissues and organs is complex. In this study, we examined the effect of the adenosine A 2A receptor agonist CGS 21680 and the A 2B R antagonist PSB-1115 on acute inflammation induced experimentally by 2,4,6-trinitrobenzenesulfonic acid (TNBS) on rat ileum/jejunum preparations. Preincubation of the ileum/jejunum segments with TNBS for 30 min resulted in a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
22
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
5
4

Relationship

5
4

Authors

Journals

citations
Cited by 21 publications
(23 citation statements)
references
References 45 publications
1
22
0
Order By: Relevance
“…As shown previously T N B S ( 1 m M -1 M ) r e s u l t e d i n a concentration-dependent inhibition of ACh-induced contractions (damage) with an IC 50 value of 63 mM. 100 mM TNBS reduced the ACh-induced contraction to approximately 35 % in comparison to intact preparation of the same animal (Michael et al, 2010). The combined preincubation of the ileum/jejunum preparation with TNBS (0.01 M, 30 min) and STW 5 (64-512 µg/ml) or STW 6 in equivalent concentrations (3-24.1 µg/ml) diminished concentration-dependently the TNBS-induced damage of the AChcontraction.…”
Section: Effects Of Stw 5 and Stw 6 On Ach-contractions In Inflamed Psupporting
confidence: 66%
“…As shown previously T N B S ( 1 m M -1 M ) r e s u l t e d i n a concentration-dependent inhibition of ACh-induced contractions (damage) with an IC 50 value of 63 mM. 100 mM TNBS reduced the ACh-induced contraction to approximately 35 % in comparison to intact preparation of the same animal (Michael et al, 2010). The combined preincubation of the ileum/jejunum preparation with TNBS (0.01 M, 30 min) and STW 5 (64-512 µg/ml) or STW 6 in equivalent concentrations (3-24.1 µg/ml) diminished concentration-dependently the TNBS-induced damage of the AChcontraction.…”
Section: Effects Of Stw 5 and Stw 6 On Ach-contractions In Inflamed Psupporting
confidence: 66%
“…The inhibition of adenosine kinase by GP515 has been explored as a potential target for the treatment of colitis [621]. In a review about purinergic receptors in gastrointestinal inflammation [403], it was concluded that P1 (A 2A and A 2B ) and P2Y receptor-based therapy is highly promising for the treatment of inflammatory conditions of the gut, as well as for fibrotic liver diseases (see [477]). Serum adenosine deaminase activity has been claimed to be a predictor of disease severity in ulcerative colitis [55].…”
Section: Inflammatory Bowel Diseasementioning
confidence: 99%
“…Preclinical studies indicated a potential of A 2B agonists for the treatment of atherosclerosis and hyperlipidemia [30]. A 2B antagonists may be useful for the treatment of asthma, diabetes, pain, and inflammatory diseases in general, although the A 2B AR has been reported to promote pro-as well as antiinflammatory effects [6,[31][32][33]. Furthermore, A 2B antagonists were proposed for the treatment of cancer and the prevention of metastasis [34,35].…”
Section: Introductionmentioning
confidence: 99%